The Government's Role in Providing Legal Protection for MSME Owners Following the Enactment of Law No. 11 of 2020 concerning Job Creation - Nikmatul Husna; Aliya Putri Hadianto; Azka Raghdah Daulay; Melinda Fitriana Siregar; Ali Rahmadi Batubara; Akhtar Safiq (ISNU Nine-Star Multidisciplinary Journal, 2025)
MSMEs are one way for people to meet their daily needs. They also play a crucial role in improving regional and national economies. However, as developments develop, MSMEs are now finding it difficult to capture market share due to competitiveness. This is further compounded by the enactment of Law No. 11 of 2020 concerning Job Creation. Therefore, the government is emphasizing legal protection for MSMEs to address the increasingly fierce competition in the current market. This study aims to analyze the government's role in providing legal protection to MSME owners following the enactment of Law No. 11 of 2020 concerning Job Creation. The main focus of this study is to explore how regulations and policies resulting from the Job Creation Law affect the legal protection provided to MSME owners, as well as the extent of the government's role in guaranteeing their legal rights, both in terms of business protection, financing, and market access. Through this study, it is hoped that various recommendations will be found that will be useful for improving government policies in providing optimal legal protection for MSME owners, as well as contributing to the development of a more sustainable MSME sector in Indonesia.